Problem-based learning (PBL) as a didactic method for the development of reading comprehension skills in the english language - Jumbo Acaro, Dayelin Anahí; Serrano Quezada, Cindy Nicole (Machala: Universidad Técnica de Machala, 2024)
This research focuses on issues with English text comprehension for foreign language students. This research used the Problem-Based Learning PBL method to enhance reading comprehension skills in tenth-grade students at the Ciudad de Machala school in 2022-2023. The teaching framework enabled using Problem-Based Learning to enhance English reading skills. This research follows a quantitative experimental approach with a pre-and post-test design. The study collected data through theoretical and empirical methods to organize and verify hypotheses using statistical graphs and chi-square.
La investigación analiza las dificultades de los estudiantes de inglés en la comprensión de textos. Se implementará el ABP para mejorar la comprensión lectora en inglés de los estudiantes de 10º grado en el colegio Ciudad de Machala durante el año lectivo 2022-2023. Se tomaron en cuenta los fundamentos educativos para crear y usar un sistema de clases basado en el método ABP. La investigación es cuantitativa con un diseño experimental pre experimental y pruebas pre y post. Se emplearon métodos teóricos y empíricos para recolectar datos y verificar hipótesis con gráficos estadísticos y el chi cuadrado.
Keywords: ENSEÑANZA; APRENDIZAJE; PROBLEMA; HABILIDAD; COMPRENSION LECTORA